Engaged leadership : building a culture to overcome employee disengagement - Swindall, Clint, 1967- 4 0 16; 5 (Hoboken, New Jersey : Wiley, 2011)
A guide for business leaders with step-by-step guidance to help associates overcome employee disengagement and reduce turnover in an organization, explaining how to create a motivating company culture, and discussing the benefits of recruiting associates to help influence a positive corporate culture, why small successes should be celebrated, and the importance of creating a balance between work and life.
Adult.
Keywords: 2 -- 0; 6; Leadership.;Employee motivation.;Leadership.;Motivation (Psychology); 20; 2